R‐CHOP‐14 versus R‐CHOP‐14/CHASER for upfront autologous transplantation in diffuse large B‐cell lymphoma: JCOG0908 study. Issue 10 (11th September 2020) - Kagami, Yoshitoyo; Yamamoto, Kazuhito; Shibata, Taro; Tobinai, Kensei; Imaizumi, Yoshitaka; Uchida, Toshiki; Shimada, Kazuyuki; Minauchi, Koichiro; Fukuhara, Noriko; Kobayashi, Hirofumi; Yamauchi, Nobuhiko; Tsujimura, Hideki; et al.
Abstract: The efficiency of upfront consolidation with high‐dose chemotherapy/autologous stem‐cell transplantation (HDCT/ASCT) for newly diagnosed high‐risk diffuse large B‐cell lymphoma (DLBCL) may be influenced by induction chemotherapy. To select better induction chemotherapy regimens for HDCT/ASCT, a randomized phase II study was conducted in high‐risk DLBCL patients having an age‐adjusted International Prognostic Index (aaIPI) score of 2 or 3. As induction chemotherapy, 6 cycles of R‐CHOP‐14 (arm A) or 3 cycles of R‐CHOP‐14 followed by 3 cycles of CHASER (arm B) were planned, and patients who responded proceeded to HDCT with LEED and ASCT. The primary endpoint was 2‐y progression‐free survival (PFS), and the main secondary endpoints included overall survival, overall response rate, and adverse events (AEs). In total, 71 patients were enrolled. With a median follow‐up of 40.3 mo, 2‐y PFS in arms A and B were 68.6% (95% confidence interval [CI], 50.5%‐81.2%) and 66.7% (95% CI: 48.8%‐79.5%), respectively. Overall survival at 2 y in arms A and B was 74.3% (95% CI: 56.4%‐85.7%) and 83.3% (95% CI: 66.6%‐92.1%). Overall response rates were 82.9% in arm A and 69.4% in arm B. During induction chemotherapy, 45.7% and 75.0% of patients in arms A and B, respectively, had grade ≥ 3 non‐hematologic toxicities. One patient in arm A and 6 in arm B discontinued induction chemotherapy due to AEs. In conclusion, R‐CHOP‐14 showed higher 2‐y PFS and less toxicity compared with R‐CHOP‐14/CHASER in patients with high‐risk DLBCL, suggesting the former to be a more promising induction regimen for further investigations (UMIN‐CTR, UMIN000003823). Abstract : The efficiency of upfront consolidation with high‐dose chemotherapy/autologous stem‐cell transplantation (HDCT/ASCT) for newly diagnosed high‐risk diffuse large B‐cell lymphoma (DLBCL) may be influenced by induction chemotherapy. To select better induction chemotherapy regimens for HDCT/ASCT, a randomized phase II study was conducted in patients with high‐risk DLBCL who had an age‐adjusted International Prognostic Index (aaIPI) score of 2 or 3. R‐CHOP‐14 showed higher 2‐y PFS and less toxicity compared with R‐CHOP‐14/CHASER in patients with high‐risk DLBCL, suggesting the former to be a more promising induction regimen for further investigations.